The approach of physiotherapists in the management of patients with persistent pain and comorbid anxiety/depression: are there any differences between male and female professionals? - G. Nicolini; M. Chiesa; M. Buoli (European Psychiatry, 2024)
Introduction Chronic pain is a prevalent condition that is frequently complicated by concomitant mood and anxiety disorders. Very preliminary data indicate that female physiotherapists could have a better attitude towards psychiatric disorders.